Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) pada Penyusunan Laporan Keuangan Satuan Kerja Pemerintah - Gultom, Corry Margaretha Jayanti; Harahap, Siti Nurwahyuningsih (Owner : Riset dan Jurnal Akuntansi, 2024)
Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) is set to be fully utilized by all ministries or agencies in 2022. A study has been conducted to evaluate the first year of SAKTI's implementation in completing agency-level financial reports. The research focused on a work unit within the Ministry of Education, Culture, Research and Technology. Qualitative research methods, including interviews, observations, and document reviews, were used to collect data. The study found that SAKTI has been effective in supporting government accounting and streamlining the process of preparing financial statements. This effectiveness was evaluated using the Human-Organization-Technology Fit (HOT-Fit Model), which assesses the human, organizational, and technological aspects of information system implementation. The study highlights the contribution of human and organizational factors in enhancing the effectiveness of SAKTI in preparing agency-level financial reports. To further improve SAKTI's effectiveness, the study suggests increasing hosting bandwidth, providing intensive training and education, and granting access to raw data.